Dual Solar Photovoltaic Fed Three-Phase Open-End Winding Induction Motor Drive for Water Pumping System Application. Issue 16 (21st October 2018) - Chinthamalla, Ramulu; Karampuri, Ramsha; Jain, Sachin; Sanjeevikumar, P.; Blaabjerg, Frede
Abstract: The distributed maximum power point tracking (DMPPT) technique is employed in most of the photovoltaic (PV) systems to achieve better conversion efficiency. There exist two basic structures to implement DMPPT technique. The first one uses multiple DC–DC converters connected to the individual PV arrays and a DC–AC inverter connected to the load. The DC–DC converters extract maximum power from each PV array independently. Whereas, the other structure avoids the use of the DC–DC converters and the DMPPT technique is implemented using the multiple DC–AC inverters. This may improve the overall efficiency and reduces the losses, cost, and size of the system. Hence, in this article, the aforesaid structure is adopted for PV pumping system which uses two DC–AC inverters connected to an open-end winding induction motor (OEWIM). Apart from the implementation of DMPPT technique, the proposed system is capable of generating four-level inverter output voltage and work under extreme environmental conditions for two PV sources, which could improve the performance of the motor drive system. The detailed design of all the major components used in the proposed system along with the operation and control are presented in this article. In support, the simulation results and the practical verification are presented.